The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1093/gerona/57.2.m122
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of an Inflammation Meter to Detect the Presence of Infection/Inflammation in Elderly Patients

Abstract: Background. Medical personnel who work in small geriatric institutions most frequently do not have access to realtime laboratory facilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…The resulting degree of cell adhesiveness/aggregation is probably a summarised effect of these proteins on the tendency of the cells to adhere to each other and aggregate. We have already shown that enhanced red blood cell adhesiveness/aggregation correlates significantly with the presence of enhanced fibrinogen concentrations 25 and with the degree of the patient's inflammatory response, 26 that it can be induced by the intravenous infusion of immunoglobulins, 27 and that it is abolished by plasmapheresis. 28 The possibility that there might be sex differences in the tendency of red blood cells to adhere to each other and aggregate has not been evaluated in a systematic way in the past.…”
Section: Discussionmentioning
confidence: 97%
“…The resulting degree of cell adhesiveness/aggregation is probably a summarised effect of these proteins on the tendency of the cells to adhere to each other and aggregate. We have already shown that enhanced red blood cell adhesiveness/aggregation correlates significantly with the presence of enhanced fibrinogen concentrations 25 and with the degree of the patient's inflammatory response, 26 that it can be induced by the intravenous infusion of immunoglobulins, 27 and that it is abolished by plasmapheresis. 28 The possibility that there might be sex differences in the tendency of red blood cells to adhere to each other and aggregate has not been evaluated in a systematic way in the past.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the erythrocytes, which are kept in their native milieu, surrounded by the various sticky proteins, are used to sense the effect of this stickiness [32,33]. This is the essence of the ERYTHROSENSE methodology and has been repeatedly shown (although by using another way of measuring the degree of cell adhesiveness/aggregation) to correlate significantly with the degree of inflammation [34] as well as the markers of the acute-phase response [35,36]. Moreover, we have recently shown that the erythrocyte aggregation in our slide test corresponds to significant inter-erythrocyte cohesive forces as examined in a shear-dependent cell flow property analyzer [37].…”
Section: Discussionmentioning
confidence: 99%
“…The test is based on the observation that multiple acute phase response proteins are involved in the induction and/or maintenance of increased erythrocyte aggregability (Weng et al ., 1996). We have recently shown that a patient's erythrocyte sedimentation rate (ESR) can be predicted with an acceptable degree of accuracy using this slide test (Rotstein et al ., 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The present study is an extension of our previous work (Rotstein et al ., 2001). We now describe two models which support the notion that a reasonable estimate of the intensity of the humoral acute phase response can be obtained from the results of the EAAT.…”
Section: Introductionmentioning
confidence: 99%